Parents' Role in Familiarizing themselves with Clean and Healthy Living Behavior in Early Childhood during the COVID-19 (Indonesian Journal of Early Childhood Education Studies, 2022)
COVID19 pandemic that continues through July 2021 is caused by the emergence of a new variant called delta with a rate higher transmission. The purpose of this study was to determine the role of parents in familiarizing young children with clean and healthy behavior (PHBS) during the COVID-19 pandemic. PHBS is the most effective way to prevent the spread of COVID-19. Parents play a very important role in familiarizing early childhood PHBS in everyday life, including washing hands before and after eating, throwing garbage in its place, eating fruits and vegetables, and doing some exercise. exercise. The method used is qualitative with a case study of three research participants, namely three mothers who have 5-6 yearold children and are currently attending kindergarten. Data collection was carried out using interview techniques. The data obtained was analyzed using thematic analysis by identifying patterns that were modeled in a phenomenon. The research results obtained are the results of a preliminary study, which shows that the role of parents in familiarization with PHBS is not optimal with regard to hand washing before and after meals, elimination of waste in their place, consumption of fruits and vegetables and exercise. Parents' efforts to familiarize themselves with PHBS are just a reminder without involving children to negotiate and make decisions regarding their children's needs for PHBS, so that children do not yet understand the benefits, impacts and the goals of the PHBS for their own health. Parents can use motion and song methods as well as digital media such as 3D animated movie videos to learn about PHBS in early childhood.